Virtual learning effects on family nursing practices during the covid-19 pandemic: evidence from undergraduate nursing students in Bandung, Indonesia - Yani, Desy Indra; Lukman, Mamat; Shalahudin , Iwan (Jurnal Keperawatan, 2023)
Introduction: Family nursing courses ensure students understand and apply relational care approaches. Objectives: This study examines the effects of family nursing virtual learning on family nursing practices among nursing students during the COVID-19 pandemic in Bandung, Indonesia. Methods: This study is a quasi-experimental study of a single group with pre-test and post-test measurements. One hundred sixty-two students who took family nursing subjects participated in this study. The family nursing virtual learning lasted 14 weeks, consisting of lectures, case studies, research tasks, and practicum. The questionnaire consisted of practical appraisal and nurse-family relationship subscales. It was measured using a ten-item instrument with response formats from 1 to 5 to indicate high to low. Wilcoxon signed-rank test was used to analyse the effect. Results: The ages of students ranged from 19-23 years, with a median of 20 (IQR = 0), and most were female (90.1%). Results showed significant differences between the pre-test and post-test with total scores of family nursing practice of (p < 0.00). Two subscales of family nursing practice also showed substantial differences in the post-test after 14 weeks of family nursing virtual learning: the practical appraisal and nurse-family relationship (p < 0.00). Conclusions: Family nursing virtual learning benefits undergraduate nursing students' family nursing practice competence.